2015
DOI: 10.1002/ca.22663
|View full text |Cite
|
Sign up to set email alerts
|

Defining the surface anatomy of the central venous system in children

Abstract: Pediatric emergency physicians, pediatric critical care specialists, and pediatric surgeons perform central venous catheterization in many clinical settings. Complications of the procedure are not uncommon and can be fatal. Despite the frequency of application, the evidence-base describing the surface landmarks involved is missing. The aim of the current study was to critically investigate the surface markings of the central venous system in children. The superior vena cava/right atrial (SVC/RA) junction, supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…This approach has many limitations because cadaveric studies do not take into account the changes incurred during the embalming process, or the effects of air in the thoracic cavity, which would have an effect on the position of thoracic structures (Hale et al ). Recently, several international studies have been published that have focused on population specific surface anatomy in living subjects by utilizing modern imaging techniques such as X‐ray, computed tomography (CT), magnetic resonance imaging (MRI), and ultrasound scanning (Emamian et al ; Chukwuemeka et al ; Kim et al , ; Soleiman et al , ; Glodny et al, ; Mirjalili et al ; Mirjalili et al ; Mirjalili et al ; Keough et al ; Subramaniam et al ; Tarr et al ). These studies reported both similarities and differences between our current anatomical knowledge and the findings of their studies.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has many limitations because cadaveric studies do not take into account the changes incurred during the embalming process, or the effects of air in the thoracic cavity, which would have an effect on the position of thoracic structures (Hale et al ). Recently, several international studies have been published that have focused on population specific surface anatomy in living subjects by utilizing modern imaging techniques such as X‐ray, computed tomography (CT), magnetic resonance imaging (MRI), and ultrasound scanning (Emamian et al ; Chukwuemeka et al ; Kim et al , ; Soleiman et al , ; Glodny et al, ; Mirjalili et al ; Mirjalili et al ; Mirjalili et al ; Keough et al ; Subramaniam et al ; Tarr et al ). These studies reported both similarities and differences between our current anatomical knowledge and the findings of their studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Subramaniam et al () provided comprehensive evidence of abdominal surface anatomy in children. Meanwhile, Tarr et al () provided an evidence‐base for the surface anatomy of the central venous system in this population.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, no specific relationship of the CVC depth of the EL and RL to patients' age was illustrated. Although the length and the position of the SVC‐RAJ were associated with age, our EL and RL were comparable to the TEE in all age‐groups. The measurement of specific patient anatomical distance as surrogated to their SVC‐RAJ distance regardless of their age may explain the satisfactory results.…”
Section: Discussionmentioning
confidence: 53%
“…In children, a clinical study found that the right third ICS had a significant correlation with the SVC‐RAJ level . An anatomical study reported that the SVC‐RAJ was usually positioned around the right third to fourth CC . Therefore, using the EL for positioning, the CVC tip at point C had a high probability of locating its tip at the lower SVC or the SVC‐RAJ level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation